DAMPAK IMPLEMENTASI SERTIFIKASI VERIFIKASI LEGALITAS KAYU TERHADAP KEBERLANJUTAN INDUSTRI KAYU DAN HUTAN RAKYAT - Elvida Yosefi Suryandari; Deden Djaenudin; Satria Astana; Iis Alviya (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
International market requires producers to proof the legality of their wood products to address the issues of illegal logging and illegal trade. Timber Legality Verification System (TLVS) has been prepared by the Government of Indonesia that covering the upstream and downstream wood industries. This paper aims to evaluate gaps in the implementation of TLVS policy and its impact on the sustainability of timber industry. This study was using gap, descriptive and costs-structure analyzes. The study was conducted in three provinces, namely: DKI Jakarta, West Java and D.I. Yogyakarta. Research found that the effectiveness of the TLVS implementation was low due to relatively rapid policy changes. This situation became disincetive for investments in timber business. Private sector perceived that TLVS policy should be applied in the upstream of timber business. Hence, the industry and market in the downstream have not been fully support to this system. Furthermore, TLVS policy implementation was considered ineffective by timber industry as well as private forest managers, especially by micro industry and smallholder private forests. This situation threatened the sustainability of timber industry and private forests. Therefore, Institutions should be strengthened in order to improve the quality of human resources and the competitiveness of products.